Productivity of Journals and the Applicability of Bradford’s Law of Scattering in Hydroponics Literature (Cuestiones de Fisioterapia, 2025)
This analysis provides a comprehensive exploration of the scientific publication landscape, highlighting thesignificance of various document types, languages, subjects, and journals in disseminating research. Articlesdominate in volume (82.82%) and citations (90.59%), with a significant average impact (CPP 28.28).Reviews, although few (2.06%), have the highest influence (CPP 62.74), while conference papers, books,and other formats serve niche roles with lower impact. English is the dominant language, accounting for91.82% of publications and 98.46% of citations, with a CPP of 27.72. Other languages like Chinese,Portuguese, and Spanish show regional relevance but lower global impact. Subject-wise, Agricultural andBiological Sciences lead (62.45%), followed by Environmental Science (27.92%) and Biochemistry, Genetics,and Molecular Biology (20.20%).Journal analysis reveals significant disparities in impact, with "Journal ofExperimental Botany" (CPP 100.37) leading in influence. Applying Bradford’s Law to hydroponics literature,28 core journals produced 33.32% of articles. However, a high error margin (16.62%) suggests deviationsfrom the law.